Health care system reforms in Hong Kong the implications of greater private sector participation - Yuen, Peter P. (1992)
The interactions between the public and private sectors constitute a major picture of the Hong Kong health care system. Recent initiatives by the government-the establishment of the Hospital Authority and the formation of a medical health insurance study group - are attempts to contain and reverse the growth of the government's involvement in financing and delivering health services. Such attempts can lead to serious cost escalations in view of the institutional and contextual characteristics of the Hong Kong health care system. The various options of health financing for Hong Kong are presented and a government regulated voluntary insurance scheme as the means to provide additional funding to the system is proposed. Under the scheme, private financing, in the form of private insurance, would play a greater role under stricter government monitoring and regulation. Mechanisms for quality assurance and cost-containment will be introduced as part of the scheme. The paper concludes by pointing out the impact that the system might have on the future health policy of the government.
Keywords: Medical care -- Hong Kong; Health care delivery; Health insurance